2016
DOI: 10.1080/0092623x.2016.1141820
|View full text |Cite
|
Sign up to set email alerts
|

Genital Self-Image and Considerations of Elective Genital Surgery

Abstract: The present study explores how genital self-image may be related to considerations of surgically altering one's genitals and documents the wanted genital changes among young adults. Evidence of a nontrivial proportion of respondents (98 of 1,110) had seriously considered elective genital surgery. Regression models indicate that, for both men and women, identifying as heterosexual and reporting lower composite genital self-image scores results in higher odds of considering genital surgery. Additionally for men,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 37 publications
0
11
1
2
Order By: Relevance
“…16 It is known that low genital self-image scores result in an increased desire for genital surgery. 17 However, in this study, no relation was detected between media exposure and direct genital perception. Using the media in an appropriate manner and education were considered to have effects in this area.…”
Section: Discussioncontrasting
confidence: 68%
“…16 It is known that low genital self-image scores result in an increased desire for genital surgery. 17 However, in this study, no relation was detected between media exposure and direct genital perception. Using the media in an appropriate manner and education were considered to have effects in this area.…”
Section: Discussioncontrasting
confidence: 68%
“…In a study by Smith et al (2017), the relationship between genital self image and Elective Genital Surgery thought was investigated. It was determined that only 98 of the 1100 participants seriously considered elective genital surgery [10].…”
Section: Studies Concerning Genital Self Imagementioning
confidence: 99%
“…Despite women and men express negative genital self image thoughts, studies mostly found that men have more positive genital self images than women. [10]. While most of the research on men's genital self image focuses on satisfaction with size, studies on the female genital self image have examined both appearance and function perceptions from an early period.…”
Section: Introductionmentioning
confidence: 99%
“…Female intimate aesthetic complaints appear due to new depilatory habits, exposing the genital area more than before. In addition, media and social networks spread the idea of bodily perfection, not just as desirable, but as integral to normative femininity [1][2][3][4]. It has been culturally assumed that the vagina has to be tight, small, and all but invisible.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, male dissatisfaction is not only restricted to their genital organ size but it may also be associated with its appearance. As a reflection of this new concern, the number of men and women seeking aesthetic treatment for their genital region has grown increasingly [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%